ANALISIS PENERBITAN SP2DK TAHUN PAJAK 2016 TERHADAP LAPORAN KEUANGAN TAHUN 2021 (STUDI PADA PT TRI PURA INDAH PERSADA) - Erica Novita Sari; Masripah - (ITB AAS INDONESIA, 2022)
Sources of state income come from natural resources and human resources taxes. Tax collection is the main choice as an alternative source of state financing. Taxes are contributions paid by the people to the state which are included in the state treasury and are regulated in laws that are bound and coercive. Several methods are used by the Directorate General of Taxes in achieving tax revenue targets by supervising taxpayers through the issuance of a letter requesting an explanation of data or information (SP2DK). The purpose of this literature is to review what factors affect the issuance and receipt of taxpayer SP2DK and their influence in recording financial statements. In addition, this research was conducted to motivate taxpayers to carry out their obligations as the color of the state. Method: Literature Review was carried out based on reference sources in the form of books or journals as well as managing research materials by observing cases or problems found. SP2DK is issued by the Account Representative for the difference in the number of figures regarding assets owned by taxpayers which so far have not been reported in the Annual SPT. Therefore, the issuance of SP2DK must have a purpose and purpose. As well as the factors causing the receipt of the SP2DK which was received by the taxpayer. After the issuance of SP2DK, of course there will be an effect of recording in financial statements related to taxes reported by taxpayers who receive SP2DK